(3OQGSGJ aj Ydhe GdecJHGJ (B/s - (3CHh TQjN, TGgQ PjHs ((3YeGf (B- (3GdCQOf (B:s (3OGQ UaGA ddfTQ hGdJhRjY ,s, 2000)
(3JWhQ fTCI Yde GdecJHGJ, CfhGY GdecJHGJ, GdOhQjGJ hGdfTQGJ, GdGYGQI, GdNOeGJ GdecJHjI, GdJhKjb hGdGQTja, GdJUfja, GdagQSI, GdeQGLY GdeYQajI, fXGe GdeOGNd ddJUfja(B.s
(3HHdjhLQGajI (B: (3UaMI (B583-584.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3eMeO(B.s
Keywords: (3Yde GdecJHGJs; (3Yde GdeYdheGJs